Can real‐time near‐infrared spectroscopy monitoring detect graft venous thrombosis after pediatric kidney transplantation?. (16th December 2021) - Ghidini, Filippo; Parolin, Mattia; De Corti, Federica; Amigoni, Angela; Fascetti Leon, Francesco; Benetti, Elisa; Gamba, Piergiorgio
Abstract: Background: A prompt detection of graft venous thrombosis might preserve the transplanted organ. A real‐time near‐infrared spectroscopy (NIRS) monitoring of the allograft perfusion could fulfill this goal. The aim of this work was to report the trend of allograft perfusion (rSO2) after pediatric kidney transplantation (KT) complicated by graft venous thrombosis. Case presentation. An infant, affected by end‐stage kidney disease due to posterior urethral valves, underwent non‐living donor KT. The allograft presented both arterial and venous variants and required a complex bench surgery reconstruction. The perfusion of the allograft was monitored by real‐time transcutaneous NIRS. The early post‐operative was conditioned by worsening clinical conditions, and a graft venous thrombosis was detected after four hours since the transplantation. NIRS monitoring lasted for 348 minutes. Median lower pole rSO2‐value was 65% (IQR 62–66%), while the median upper pole rSO2‐value was 70% (IQR 70–71%). These data reflected the congestion of the lower pole, observed at the end of the transplantation. The lower pole showed inferior rSO2 values ( p <0.0001). At the end of the monitoring, the decrease in peripheral rSO2, measured in left lower limb as a benchmark, was consistent with the ongoing hypovolemic shock and severe acute anemia. Conclusion: Transcutaneous NIRS might be a reliable device for monitoring allograft and peripheric perfusion after pediatric KT. The modifications of rSO2 values helped the clinicians manage the patients in the post‐operative and early detect acute complications.